Testicular protective and antioxidant effects of selenium nanoparticles on Monosodium glutamate-induced testicular structure alterations in male mice - Reham Z. Hamza (Toxicology Reports, 2020)
Background: Selenium has a protective antioxidant effect on several tissues. Monosodium glutamate (MSG), MSG has been known as flavor enhancer that influences reversely on male reproductive systems and having a number of side effects, including reproductive toxicity. Objectives: The current study aims to evaluate the possible ameliorative functions of selenium nanoparticles (SeNPs) on MSG-induced reproductive toxicity. Materials and methods: In total, 42 male mice included in this study were divided into six groups: control, MSG (LD), MSG (HD), SeNPs, MSG (LD) plus SeNPs and finally MSG (HD) plus SeNPs. Testosterone hormone, tumor necrosis factor-alpha (TNF-α), as well as the antioxidant biomarkers: superoxide dismutase [SOD], glutathione peroxidase [GPx], catalase [CAT] and marker of lipid peroxidation [MDA], were examined. Histological and comet assay variations in the testicular tissues as markers of testicular damage after the MSG administration in two doses (MSG-LD and MSG-HD) either alone or combined with SeNPs.MSG in two doses (LD and HD) genotoxic effects were also evaluated and the ameliorative role of SeNPs on the testicular tissues were recorded. Results: Results proved that the administration of SeNPs diminished the effect of MSG (LD and HD)-that induced decrease in testosterone hormone levels and elevated oxidative stress markers markedly. SeNPs had a potent antioxidant effect and elevated the antioxidant enzymes significantly and decreased lipid peroxidation markers as compared with MSG either (LD and HD) groups. Conclusion: It is clear from the data that SeNPs inhibit testicular injury and improve the antioxidant state in male mice.